Ace school

with brainly

  • Get help from millions of students
  • Learn from experts with step-by-step explanations
  • Level-up by helping others

A community for students.

What is the solution to the equation?

Mathematics
See more answers at brainly.com
At vero eos et accusamus et iusto odio dignissimos ducimus qui blanditiis praesentium voluptatum deleniti atque corrupti quos dolores et quas molestias excepturi sint occaecati cupiditate non provident, similique sunt in culpa qui officia deserunt mollitia animi, id est laborum et dolorum fuga. Et harum quidem rerum facilis est et expedita distinctio. Nam libero tempore, cum soluta nobis est eligendi optio cumque nihil impedit quo minus id quod maxime placeat facere possimus, omnis voluptas assumenda est, omnis dolor repellendus. Itaque earum rerum hic tenetur a sapiente delectus, ut aut reiciendis voluptatibus maiores alias consequatur aut perferendis doloribus asperiores repellat.

Join Brainly to access

this expert answer

SIGN UP FOR FREE
|dw:1355183253471:dw|
Let f(x)= –2x + 4 and g(x) = –6x – 7. Find f(x)–g(x).
f(x) = 3x – 7 and g(x) = –2x – 6. Find (ƒ ∘ g)(4) What is the inverse of the given relation? y = 3x + 12

Not the answer you are looking for?

Search for more explanations.

Ask your own question

Other answers:

|dw:1355183442460:dw|
@nubeer can u help with these?? I need the whole worked out solution ):
|dw:1355183843739:dw|
You square both sides of the equation so you get rid of the radical sign on the left.
|dw:1355184226259:dw|
Just x = 0
OH ok, can you help me with these? Let f(x)= –2x + 4 and g(x) = –6x – 7. Find f(x)–g(x). What is the inverse of the given relation? y = 3x + 12
|dw:1355184624673:dw|
@julliemyers What work have you done on these problems so far? It's hard to help out if I don't know what you already know and can do. :)
f(x) = 3x – 7 and g(x) = –2x – 6. Find (ƒ ∘ g)(4) (fo g)(4) f(g(4)) G(x)=-2x-6g(4)=-2*(4)-6g(4)=-8-6 g(4)=-14 f(g(4))=f(-14) f(x)=3x-7 f(-14)=3*(-14)-7 f(-14)=-42-7 f(-14)=-49 (f o g)(4)=-49
@mathteacher1729 is that correct?
@julliemyers Yup, that is correct! :) And your reasoning is very clear as well.
What is the inverse of the given relation? y = 3x + 12 =3x=y-12 =x=y/3-4 =y=x/3-4 @mathteacher1729 correct?
f(x) = –2x + 4 and g(x) = –6x – 7 f(x) – g(x) (-2x+4) – (-6x –7) -2x+4+6x +7 4x+11
@julliemyers Yuppers on the inverse problem.
f(x) = –2x + 4 and g(x) = –6x – 7 it might be 8x+11 and not 4x+11 >.>
|dw:1355185571096:dw|

Not the answer you are looking for?

Search for more explanations.

Ask your own question